Study of the Physical Properties of Pinus Halepensis of Oran. Application to the Flammability - Boutchiche, H.; Sabi, F. Z.; Mosbah, O.; Sahila, A.; Terrah, S.M.; Zekri, N. (Algerian Journal of Research and Technology (AJRT), 2020)
Physical parameters (density, packing ratio etc.) of pinus halepensis needles harvested from the campus of Université des Sciences et de la Technologie d’Oran are measured and used in a simple physical model for ignition. The numerical results obtained by the model are compared with ignition time measurements for the same fuel using a cone calorimeter. The ignition time seems over-estimated by the model. Further discussions on the reasons of this discrepancy are provided.